(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The concern of urban communities towards health continues to increase and can be proven by the growth of health insurance 10-15%, the birth of the Indonesian Gardening community and other healthy lifestyle communities. Air pollution is a major factor causing health problems, because indoor air pollution is 2-5 times (Vidyautami, et al., 2015) worse than outdoors and humans spend 90% of their activities indoors. NASA scientists in the 80s conducted a study of the role of plants in the room to eliminate organic chemicals in the air just by placing air purifier plants in a room with a height of 20cm making a very large reduction for air pollution. But it is not easy to care for these ornamental plants when they are placed in a room. Obstacles to moving ornamental plants from the yard into the room include, in addition to adjusting the types of plants, a pot that can be adjusted to the conditions of the room is also needed. In this design the author aims to be able to make a pot that can adjust to the busyness of the urban community that can facilitate the process of plant maintenance every day.